2017
DOI: 10.1080/09654313.2017.1306028
|View full text |Cite
|
Sign up to set email alerts
|

Local culture as a context for entrepreneurial activities

Abstract: This paper examines how an industrial legacy leads to the formation of a distinct local culture and how the culture's survival provides a context for the subsequent entrepreneurial activities in new local industries. The discussion about culture as a key driver of entrepreneurship and economic growth is well established in the academic debate. However, we know little about how culture is formed. Through a qualitative case study of two polar Swedish cities, the study highlights four key factors which are instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…A growing number of recent scholars (Krueger et al, 2013;Hopp and Stephan, 2012) believe that culture can no longer be equated with nation, primarily because of widespread multiculturalism and immigration. Different sub-cultures exist within any given country (Davidsson and Wiklund, 1997;Garcia-Cabrera and Garcia-Soto, 2008;Levie, 2007), and scholars have consistently stressed on the importance of local and regional culture in the study of entrepreneurship (Gunnerud, 1997;Lang et al, 2014;Fredin and Jogmark, 2017;Hofstede, 2001). Several scholars have argued that compared with national culture, community-level cultural norms reflect a more proximal context within which entrepreneurial action takes place (Hopp and Stephan, 2012;Aoyama, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of recent scholars (Krueger et al, 2013;Hopp and Stephan, 2012) believe that culture can no longer be equated with nation, primarily because of widespread multiculturalism and immigration. Different sub-cultures exist within any given country (Davidsson and Wiklund, 1997;Garcia-Cabrera and Garcia-Soto, 2008;Levie, 2007), and scholars have consistently stressed on the importance of local and regional culture in the study of entrepreneurship (Gunnerud, 1997;Lang et al, 2014;Fredin and Jogmark, 2017;Hofstede, 2001). Several scholars have argued that compared with national culture, community-level cultural norms reflect a more proximal context within which entrepreneurial action takes place (Hopp and Stephan, 2012;Aoyama, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Very few empirical studies have examined the association between culture and entrepreneurship at the regional level (Hayton et al, 2002;Hopp and Stephan, 2012). The available studies (Davidsson, 1995;Davidsson and Wiklund, 1997;Fredin and Jogmark, 2017) have indicated a significant association between local cultures and the regional rate of new firm formation. This study takes the above-mentioned concerns into consideration and attempts a formal investigation on the role of gender and regional culture on the perceived barriers to entrepreneurship and entrepreneurial intentions in the two culturally diverse regions of Garhwal and Kumaon, which belong to the same state of Uttarakhand and are under a single government.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, these studies that analyse cultural evolution based on personality traits are critical in understanding the origin and effects of regional business culture. They highlight the usefulness of approaching personality in studying economic environments (Fredin and Jogmark, 2017).…”
Section: Geographical Area and Regional Culturementioning
confidence: 99%
“…Controversies persist over whether entrepreneurship can be taught or not (Kuratko, 2005), or the role of gender or family background in the likeliness to become an entrepreneur (Wang & Wong, 2004;De Martino & Barbato, 2003), or whether local culture has an influence on entrepreneurial activities (Fredin & Jogmark, 2017). In general, the literature has focused on entrepreneurship as an individual trait, whether in inherited or learned, relatively neglecting the collective nature of the entrepreneurial phenomenon (Schumpeter, 1951).…”
Section: Practicementioning
confidence: 99%